Cyber Bullyingin Social Media Against the Stigma of Indonesian Women's Beauty Standards - Widiandaru Wiryawan; Sintia Catur Sutantri (International Journal of Education, Information Technology, and Others, 2023)
This article examines Cyber Bullying on Social Media against the stigma of Indonesian women's beauty standards. The discussion in this study regarding the impact of social media on the formation of social stigma on women's beauty standards in Indonesia as a means of causing Cyber Bullying. This research method uses a qualitative method that is used to describe the data that has been obtained regarding cyber bullying against women's beauty standards in Indonesia. This article concludes that the role of social media is very large in applying women's beauty standards in social media as well as being a source of Cyber Bullying